Quantitative identification of non-point sources of nitrate in urban channels based on dense in-situ samplings and nitrate isotope composition. (January 2021) - Guo, Jiaxun; Zuo, Ping; Yang, Long; Pan, Ye; Wang, Lachun
Abstract: Quantitative identification of non-point sources of nitrate in urban channels plays a critical role in effective nutrient management in urban regions. This is an emerging issue due to fast urbanization and the resultant complicated hydrological and hydraulic conditions in urban areas. In this study, we examine spatial-temporal characteristics of nitrogen concentration in urban channels based on dense in-situ samplings during a one-year period over a small urban catchment in China. We quantitatively identify nitrate sources into urban channels based on dual-isotope analyses and Bayesian isotope mixing model. Results show that nitrogen concentration peaks in winter as well as in urban channels and land surfaces in the urban core region. Sewage (47%) is the dominate contributor to NO3 − -N in urban channels, followed by NH4 + in fertilizer (30%) as the second contributor. Sewage (NH4 + in fertilizer) contributes more NO3 − -N to channels in winter (summer) with the proportion of 65% (44%), and more NO3 − -N to urban core (suburban) channels with the proportion of 59% (42%). The rainfall and distribution of rainwater drains explain the monthly and spatial variations of contribution of NO3 − -N sources well, respectively. In addition, less NO3 − -N in the urban channels derives from nitrification, which is consistent with the results of high properties of NH4 + -N/TN in this region. Our results highlight the key roles of land use types and rainfall in NO3 − -N source apportionment, and provide support for the nitrogen management practices in urbanized regions. Graphical abstract: Image 1 Highlights: The contributions by sewage significantly varied in space and season. NO3 − -N mainly sources from sewage (fertilizers) in winter (summer). Sewage contributes more NO3 − -N to the channels in urban core.